Recover : an investigation into a possible counter strategy that challenges destructive spatial practices in contested urban territories by cultivating networks of opportunity (applied in a South African urban context) - Botes, Nico (University of Pretoria, 2013)
Dissertation (MInt(Prof))--University of Pretoria, 2009.